1850-51 N.C. Sess. Laws 243 - (:unkn) unknown (My University, 1850)
Ch. 121, § 5: Applied a property tax on all pistols, Bowie-knives for one dollar. A property tax of fifty cents applied to dirks, sword canes.
Keywords: TAX - PROPERTY OR SALES